Factors that affect the transmission risk during contact with multi drug resistant tuberculosis. Issue 1 (2010) - Abakay, Abdurrahman; Tanrıkulu, Abdullah Çetin; Abakay, Özlem; Şenyiğit, Abdurrahman; Işık, Recep
No abstract available